RESULTS OF THE SURVEY CONDUCTED AMONG OPHTHALMOLOGISTS ON THE ISSUE OF EQUIPMENT OF MEDICAL INSTITUTIONS WITH OPHTHALMOLOGY DEVICES - S. V. Seraphimov (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Introduction. The problem of limited accessibility and quality of ophthalmic medical care remains one of the leading ones in the national healthcare. This article presents results of the survey conducted among ophthalmologists about the effect of large-scale equipment of all medical institutions in the Leningrad Region with modern ophthalmologic devices over the recent years.Objective is to determine the contribution of the health care modernization program to equipping the medical institutions of the Leningrad Region with modern ophthalmologic medical devices, and to identify the main areas for improving the ophthalmologic care for residents of the Leningrad region with cataracts.Materials and methods. According to a specially developed questionnaire, 105 ophthalmologists from the Leningrad Region were interviewed. The survey was conducted among physicians working both in out-patient medical facilities and in medical facilities with in-patient modalities.Results. The results of the study confirmed positive changes that occurred in recent years as a result of equipping medical institutions with modern medical devices. Almost two-thirds (59.9%) of respondents noted that equipping with modern medical devices had a significant impact on the quality of the medical and diagnostic measures carried out in healthcare facilities of the region.Conclusions. The equipment had a significant impact on the diagnosis and treatment of all kinds of diseases of the eye and its appendages, especially such eye disease which is so common among the population of the Leningrad Region as cataracts (75.0 per 100 ophthalmologists surveyed). At the same time, in spite of these efforts, the standard for equipping ophthalmologic departments in individual medical institutions has not been fully provided. Only every fifth (20.9%) ophthalmologist noted during the survey that the list of available ophthalmic devices was sufficient, and that they all worked properly.